ARIMA-Based Analysis of Financial Risks in Islamic and Conventional Rural Banks - Ahmad Syathiri; Fera Widyanata; Farida Kumalasari; Heru Wahyudi (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze and compare the financial risks of Islamic Rural Banks (BPRS) and Conventional Rural Banks (BPR) in Indonesia, focusing on liquidity and credit risks. The objective is to provide a comprehensive understanding of risk management patterns and performance differences between these two types of banks. Methodology/approach: This study aims to analyze and compare the financial risks of Islamic Rural Banks (BPRS) and Conventional Rural Banks (BPR) in Indonesia, focusing on liquidity and credit risks. The data analysis used is time series analysis with the ARIMA method. Results/findings: The findings reveal that BPRS generally maintains higher liquidity ratios with lower liquidity risk compared to BPR, although both bank types exhibit credit risk above the recommended threshold. The forecasting results indicate that BPRS is likely to maintain its liquidity and reduce non-performing financing in the coming period, while BPR faces declining liquidity and persistent non-performing loan issues. Conclusion: Islamic and conventional rural banks show different financial risk profiles, with conventional banks facing higher liquidity and loan risks, while Islamic banks generally maintain stronger liquidity but remain exposed to financing risks. Limitations: This study is limited by its focus on quantitative indicators and historical data, without incorporating qualitative or macroeconomic factors. The use of ARIMA may not fully capture sudden structural changes or regulatory impacts. Contribution: The study offers insights for improving risk management and compares Islamic and conventional rural banks in a developing country.